Reforming Parliamentary Democracy - Seidle, F. Leslie; Docherty, David C. (...David Campbell...) (MQUP, 2003)
The authors address issues of representation - the move to a proportional electoral system in New Zealand, the unsuccessful attempt to establish a domestic head of state in Australia, and the reform of the British House of Lords - and demonstrate that citizens increasingly want legislative institutions to more closely reflect the societies they serve. To discuss responsiveness, the governance of indigenous communities and their place within the broader society in Canada and New Zealand are examined, as is the role of institutions other than legislatures that are involved in protecting minority rights and responding to various forms of diversity. A separate chapter analyses the basis for and merits of proposals to reform the Canadian House of Commons. In addition, authors review the dynamics of federalism, intergovernmental relations, and other processes of multi-level governance in Canada, the United Kingdom, and South Africa. Public debate about adapting governance processes to changing conditions and citizen values is a necessary condition of successful democracies and there is much to learn from progress and false starts in other parliamentary democracies. Contributors include Jonathan Boston (Victoria University of Wellington, New Zealand), Paul Chartrand (consultant, Victoria, British Columbia), Stéphane Dion (minister of Intergovernmental Relations, Government of Canada), David Docherty, Mason Durie (Massey University), Robert Hazell (University College London), Christina Murray (University of Cape Town), Cheryl Saunders (University of Melbourne), Leslie Seidle, Jennifer Smith (Dalhousie University), and Lord Wakeham (former chairman of the Royal Commission on House of Lords Reform).